PERUBAHAN SIFAT MEKANIS DAN STRUKTUR MIKRO BAJA JIS G4051 S15C AKIBAT HARDENING DENGAN VARIASI MEDIA PENDINGIN - Nofri, Media (Bina Teknika, 2017)
Testing is an experiment to know the change of mechanical properties and micro structure in JIS G 4051 S 15 C series steel which is previously was cooled with some variation of media such as immersion into water, oil and cooling in free air then the test include: chemical composition, hardness , Impact, Fractography and Metallography. From result of testing the chemical composition with main integer element got result: 0.15% C, 0.157% Si, 1.2% Mn, 0.01% P, 0.02% S. Hardness test results with Vickers method obtained 183 HV for original test object (original) , 182.66 HV for water-cooled test specimens, 190.33 HV cooled with oil and 196.33 HV cooled with air. While in the impact test the toughness value is 0.5 Joule / mm2 for the original test object, 0.39 Joule / mm2 water-cooled test specimens, 0.56 Joule / mm2 oil-cooled specimen, and 0.61 Joule / mm2 cooled test object With free air. In Fractography testing can not be further analyzed the type of fracture, because the photo does not showed the form of cracks or fault plot. While the metallographic results for the original test object or non heat treatment structure is Ferrite and Pearlit, after Hardening the structured remains Ferrit and Pearlit, there is a change in the structure form into Martensit. The mechanical properties generated after the testing process on the JIS G 4051 S 15 C steel have increased the toughness and decreased the hardness so that the steel can be summarize to be more resilient than the original.